Hybrid problem recognition techniques for palm oil mills maintenance - Hassan Basari, Abd. Samad (Penerbit UTM, 2007)
Maintenance problem recognition is a process of identifying, defining, and diagnosing industrial maintenance problems. The main purpose of maintenance problem recognition is to avoid tackling the wrong problem. Generally maintenance problem recognition involves (Christer and Whitelaw, 1983): a) Identifying the existence and location of the problem: Which are recognising the symptoms, seriousness of the problem from the aspect of cost, downtime as well as the size, and the areas of the fault in the plant’s machines where the problems are most developed.b) Determining the problem’s causes: The analysis of the problem’s causes can be at structural or functional level. Consequently depending on the level of causal analysis, different solution strategies may be generated. c) Generating and determining possible solution strategies. Having identified problem and its nature, location, causes and consequences, then possible solution strategies could be developed or generated.